Linguistic Ambiguity in The Lyrics of Ariana Grande’s song : A Literary Interpretation - Risna Tamrin; Rindu Ainum; Winda Limbong Gayang; Bahar Bahar; Basri Basri; Fitriana Fitriana (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aims to identify types of linguistic ambiguity in Ariana Grande’s songs using Stephen Ullmann’s framework and to interpret the multiple meanings created in the lyrics. Using a qualitative textual analysis, the research examines five songs Supernatural, No Tears Left to Cry, Break Free, Bloodline, and 7 Rings. The data consist of official lyrics obtained from AZLyrics and analyzed through identification, classification, and interpretation stages. The findings show two types of ambiguity: lexical ambiguity, which is dominant through polysemy, metaphors, and unclear pronoun references, and grammatical ambiguity through structures such as double negatives. Phonetic ambiguity does not appear. The study concludes that ambiguity is intentionally used as an artistic strategy, enriching emotional depth and expanding interpretive possibilities for listeners.